Sie sind auf Seite 1von 6

PHYSICS 110A : CLASSICAL MECHANICS

HW 4 SOLUTIONS

(2) Taylor 7.14

For the yo-yo the kinetic energy will have a rotational and translational motion:
1 1
T = mv 2 + I 2 .
2 2
Now in our coordinate system v = x and = . We also know the moment of inertia for a
solid disk is I = 21 mR2 . Finally since the rope does not slip as the yo-yo falls we can say
v = R (remember this equation?), or for us x = R. Altogether we have:
   2
1 2 1 1 2 x 3
T = mx + mR = mx2 .
2 2 2 R 4
Our potential energy is:
U = mgx.
So out Lagrangian is:
3
L = mx2 + mgx.
4
using the Euler-Lagrange equation we find:
2
x = g.
3

(3) Taylor 7.27

Here the kinetic energy is (please see figure 1):


1 1 1
T = 4mx2 + m(x + y)2 + + 3m(x + y)2 = 4mx2 + 2my 2 + 2mxy.
2 2 2
And our potential will be:

U = 4mgx mg(l1 x + y) 3mg(l1 x + l2 y) = mg2y.

Where we dropped any constants. So our Lagrangian is:

L = 4mx2 + 2my 2 + 2mxy mg2y.

After we Euler-Lagrange it we have:

4x = y.

1
x

y
4m

3m

Figure 1: Figure for 7.27.

And:
2y + x = g.
You can solve these coupled equations to get:
g
x = .
7

(4) Taylor 7.33

We find the kinetic energy for the bar of soap (useful for making money to sustain your
fight club). There is both a rotational and translational term (please see figure 2).
1 1
T = mx2 + mx2 2 .
2 2

2
Where x is the distance from the soap to the edge of the plate. And our potential will be:

U = mgx sin(t).

So our Lagrangian:
1 1
L = mx2 + mx2 2 mgx sin(t).
2 2
Remember is a constant.

After we Euler-Lagrange it we have:

mg sin(t) + mx 2 mx = 0.

Or:
x 2 x = g sin(t). (1)
For the solution it is suggested to try a technique similar to what we used to solve equation
5.48 in the text. Here we try a solution of the form:

x
wt

Figure 2: Plot keeping 4 terms.

x(t) = xp (t) + xh (t).

The homogeneous equation is:


x 2 x = 0.
The solution to this is:
xh (t) = c1 e(t) + c2 e(t) .
Or similarly:
xh (t) = r1 cosh(t) + r2 sinh(t).
And for the particular solution they suggest trying:

xp (t) = A sin(t).

Plugging this into equation (1) we get:

2 A sin(t) 2 A sin(t) = g sin(t).

Solving for A we have:


g
A= .
2 2

3
So our solution looks like:
g
x(t) = r1 cosh(t) + r2 sinh(t) + sin(t). (2)
2 2
We have initial conditions:
x(0) = x0 ,
and
x(0) = 0.
These combined with equation (2) lead us the the solution for x(t):
g
x(t) = x0 cosh(t) + (sin(t) sinh(t)) . (3)
2 2

(5) Taylor 7.36

(a) The kinetic energy will be:


1 1
T = mr2 + mr2 2 ;
2 2
and the potential energy will be:
1
U = k(l0 r)2 mgr cos .
2
So our Lagrangian is:
1 1 1
L = mr2 + mr2 2 k(l0 r)2 + mgr cos .
2 2 2
(b) From the Euler-Lagrange equations we get:
k
r = r2 + g cos + (l0 r);
m
and:
d h 2 i
r = gr sin .
dt

(c) Now we are asked to solve these equations for small oscillations. For small oscillations
these equations become:
k
r = g + (l0 r); (4)
m
And:
d h 2 i
r = gr. (5)
dt
Setting equation (4) equal to zero we find the equilibrium value or r is r0 = m
k g + l0 .

4
Now we will expand for small values of r by setting r = r0 + .
We have:
k
(r0 + ) = g + (l0 r0 );
m
Or:
k m
 = g + (l0 g l0 ).
m k
And finally:
k
 = ;
m
k
Where we have the equation for simple harmonic motion with 2 = m. And for equation
(5) expanding out we have:
g
= . (6)
r0
g
Where we have the equation for simple harmonic motion with 2 = r0 .

(6) Taylor 7.37

r
f

Figure 3: Figure for 7.37.

(a) The kinetic energy will be:


1
T = mr2 + mr2 2 .
2
Note: here we have two blocks that will have translational kinetic energy. And the potential
energy will be:
U = mgr.
So our Lagrangian is:
1
L = mr2 + mr2 2 mgr.
2

5
(b) From the Euler-Lagrange equations we get:

2r = r2 g. (7)

And:
d h 2 i
mr = l.
dt
Where l is a constant we know as the angular momentum. So in this problem the angular
momentum is conserved. Solving for we have = mrl 2 . Lets plug this into equation (7)
to get:
l2
2r = 2 3 g. (8)
m r
(c) To find the equilibrium position we set r = 0 in equation (8) above. Therefore:
s
l2
r0 = 3 2 . (9)
m g

Physically if you plug the definition of l back in to equation (9) you get:

g = r2 .

Which is to say the gravitational acceleration of the falling block is equal to the centripetal
acceleration of the rotating block.

(d) Finally we want to expand for small oscillations r = r0 + . So we have:

l2
2
= g.
m2 (r0 + )3

Or:
l2
2
=  3 g.
m2 r03 (1 + r0 )

Or:
l2 
2
= 2 3 (1 3 + ...) g.
m r0 r0
But due to equation (9) we have:
3l2
 = .
2m2 r04
q
3 l
Where we have the equation for simple harmonic motion with 2 = 2 mr02 .